Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/1758834014534515
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions and patient burden in chemotherapy-induced anaemia in France

Abstract: In France, CIA treatment with RBC transfusion is a time-consuming activity for patients that includes multiple trips to a medical facility, blood testing and the transfusion procedure itself. This burden is important to consider in the context of optimizing proactive monitoring and planning for supportive oncology care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
(30 reference statements)
0
18
0
1
Order By: Relevance
“…More specifically, prophylactic treatment with G‐CSF is generally recommended when the risk of FN is considered to be high (>20%) based on the chemotherapy regimen and patient risk factors, and has been shown to reduce the risk of FN and early mortality without significantly affecting antitumour responses. However, each of these interventions is associated with its own set of associated side effects and/or a burden to patients' quality of life 35,37‐39 . In our study, reductions in the use of G‐CSFs, RBC transfusions and ESA administrations all favoured trilaciclib over placebo, indicating a decrease in the risk of clinically significant, multilineage CIM.…”
Section: Discussionmentioning
confidence: 62%
“…More specifically, prophylactic treatment with G‐CSF is generally recommended when the risk of FN is considered to be high (>20%) based on the chemotherapy regimen and patient risk factors, and has been shown to reduce the risk of FN and early mortality without significantly affecting antitumour responses. However, each of these interventions is associated with its own set of associated side effects and/or a burden to patients' quality of life 35,37‐39 . In our study, reductions in the use of G‐CSFs, RBC transfusions and ESA administrations all favoured trilaciclib over placebo, indicating a decrease in the risk of clinically significant, multilineage CIM.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, only 21% of survey participants in the current study reported receiving no treatment. This finding is notable, as the supportive care interventions themselves can present additional risks, such as bone pain with G(M)-CSF; thrombotic events with ESAs; and transfusion reactions and infections with RBC and platelet transfusions; as well as being a burden to patients [7,8,[24][25][26]33]. Approximately two-thirds of survey participants experienced an issue with continuing on their current chemotherapy regimen due to myelosuppression, reflecting the substantial impact of hematologic side effects on standardof-care treatment schedules and doses.…”
Section: Discussionmentioning
confidence: 99%
“…One survey of 15,785 adult cancer patients assessed the burden of time associated with medical visits for the management of chemotherapy-induced anemia (CIA) and neutropenia on patients and caregivers, and found that each visit involved approximately 2 h for the patient and over 1 h for caregivers [24]. Likewise, several surveys conducted to determine the impact of blood transfusions on patients with CIA have concluded that the time spent travelling to medical facilities, along with blood testing and the procedure itself, presents a considerable burden to patients [24][25][26]. While these studies highlight the logistic burden associated with CIM, there remains a need for more research into the broader impact that CIM and its management has on patients' lives, and to raise awareness among patients regarding the contribution of CIM to the overall toxicities associated with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective observational cohort study monitoring vital signs during transfusions and transfusion-associated circulatory overload, vital signs were monitored at 15 minutes after the transfusion started and at completion (Andrzejewski et al, 2012). A study on transfusion for chemotherapyinduced anemia noted that the lapse between pre-and post-transfusion vital signs was four hours (Corey-Lisle et al, 2014). Two studies included frequencies for monitoring that did not provide specific time frames (Gammon, Waters, Watt, Loeb, & Donini-Lenhoff, 2011), of which one (Anyaegbu, 2011) emphasized the importance of documenting pre-transfusion vital signs and monitoring and documenting recipient vital signs, as well as any adverse reaction during and after the transfusion.…”
Section: Summary Of the Evidencementioning
confidence: 99%